MINIATURE SURFACE TRACING DEVICE FOR SURGICAL GUIDANCE AND NAVIGATION - MOHD YUSOFF, MUHAMMAD AIZAT (2018)
Inertia Measurement Unit (IMU) sensors are being used in moveable application. The concept of the quaternion is used in this project as it will explain how the 3 dimensional work. Inertia Measurement Unit is one of the tools that is needed as it can illustrate the 3 dimensional orientation by having 3 sensors which are gyroscope, accelerometer and magnetometer. These sensors will help the system to trace the movement during 3D surface mapping process. The positioning algorithm is being applied in order to obtain the displacement and angle of an object for each axis. A simple integration need to be implemented to the inertial sensors. The double integration of the acceleration obtained from the accelerometer will provide the displacement travelled of an object through the axis while a single integration of the angular velocity obtained from the gyroscope will give angle information that the object rotating in the axis. However, due to the noise and the disturbance from the surrounding will affect the accuracy that was obtained from the integration. In order to reduce the noise, the sensors were being calibrated. Then, the 3-dimensional of the IMU board is being illustrated using the Processing software.